Pediatric palliative care team perceptions’ about hospital clowns - Valdebenito Mac Farlane, Victoria (Acta Bioethica, 2021)
This is a synthesis of results of a major research which main objective was to know the perspectives of families and the health team regarding the presence of hospital clowns working in pediatric palliative care in a unit in Chile. Guided by an interpretivist paradigm, strict quality and ethical criteria, the methodology used was qualitative, applying in-depth interviews, document analysis and discussion groups as data collection techniques. The data section presented here about the health team was analyzed through content analysis and critical discourse analysis techniques. The results indicate that the figure of the clown is perceived as a mediator, valued as complementary therapy, especially due to the socio-emotional competences of these professionals and play used as an intervention tool. The conclusions indicate that the socio-emotional competences promoted by the hospital clown are fundamental to work in palliative care.